AB0289 The Degree of Discordance between Global Estimates by Patients and their Physicians in Various Rheumatic Diseases. (10th June 2014) - Celik, S.; Castrejon, I.
Abstract : Background: In rheumatic diseases, quantitative assessment including estimates of global status by physicians (DOCGL) and patients (PATGL) is required since there is no any single gold standard biomarker measure for optimal management of the diseases and ideally, these estimates should be concordant. Objectives: To examine the degree of discordance between DOCGL and PATGL and variables contributing to discordance in rheumatic diseases Methods: A PubMed search was conducted with the restrictions of "Human" and "English" up to February 2013. Randomized Controlled Trials (RCTs), Cohort Studies, reviews and Meta-analysis were included. The studies including patients with rheumatic diseases comparing DOCGL vs PATGL were selected. The primary outcome was the percentage of concordance/discordance of PATGL and DOCGL. Two reviewers screened title/abstracts independently and collected data Results: From 355 initial studies captured, 321 were excluded after reading title/abstract. 34 were selected for further review and finally 3 studies with rheumatoid arthritis (RA), 3 studies with systemic lupus erythematosus (SLE) and 1 study with juvenile idiopathic arthritis (JIA) were included. The cut-points for the discordance were variable between the studies (from 1 to 3). While the range of concordance between patients and physicians was 28.7 to 78%, PATGL>DOCGL was 2 to 43.7% and DOCGL>PATGL was 5 to 51.3%. In general, while the variables contributing to discordance for PATGL>DOCGL were poor function, high age, pain, morning stiffness and poor mental health, the explanatory variables for the DOCGL>PATGL were abnormal laboratories and high swollen, tender joint counts (Table 1 ). Conclusions: The concordance rates between the patients and physicians on global estimates in many rheumatic diseases were low. Discordance has been reported to be associated with poorer outcomes. To record both the patient and physician global estimates at each visit can play an important role to improve the concordance between them. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.6040